The Evaluation of Sweetness, Starch and Sugar Concentrations of Ipomoea Batatas L. cv. Rancing from Specific Location in the Villages of Cilembu and Cimaung - Erly Marwani; Risti Desiyanti; Yeyet Setiawati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
In order to examine the potency of a non-typical land for cultivation of Cilembu sweet potato (Rancing cultivars of I. batatas) to generate a similar sweet taste with that when planted in its typical land, evaluation of sweetness, sugar and starch concentration of the cultivated sweet potato was carried out at Cimaung and Cilembu villages. Results indicated that concentration of starch in the fresh tuber that harvested at Cilembu and Cimaung were 37% and 35%, and decreased to 19.6% and 31.5%, within 5 weeks after storage, respectively. High Pressure Liquid Chromatography analysis showed that fresh sweet potato consisted of soluble sugar of fructose, glucose and sucrose, while baked sweet potato showed the presence of maltose, fructose, glucose and sucrose. The total soluble sugar in the freshly harvested sweet potato from Cilembu was higher than that of Cimaung, 4.0% compared to 2.6% and reach maximum to 9.4% and 6.0%, at 4 weeks after storage. Principle component analysis indicated that starch and sugar content significantly showed positive correlation with elevation, rainfall, soil nutrient content, C/N ratio and cation exchange capacity levels. The tubers produced from Cilembu had sweet taste, while those from Cimaung had normal taste.